Artificial Intellegence in Smart-Home System using Power over Ethernet (PoE) - Utami, Sri; Rahardjo, Agoeng Harjatmo; Mursanto, Wahyu Budi (Jurnal Internasional Penelitian Teknologi Terapan, 2024)
Smart homes have been developed for the convenience and efficiency of energy use. Excessive lighting is one of the causes of wasted energy consumption. Smart light control is a solution. However, the control device used needs to be placed in the several points needed to turn on the lights, run the controller and the communication media so that the controller can adjust the lighting. This is very difficult during installation because an electric line is required to each light point. There are many AC / DC adapters for each light controller and there will be additional cables if a cable is used for the communication line. This study examines the use of Power over Ethernet (PoE) which is used for smart lamp installations where the ethernet data communication cable is not only used for communication but also used to transmit DC power to regulate lamp lighting. Whereas for room lighting settings, a reading of how much light intensity the room is used is so that it can be determined the number of lights that need to be turned on. The combination of smart home intelligence and easy system installation with PoE is the focus of this research.